2006
DOI: 10.1103/physrevlett.96.230404
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Vanishing of the Order Parameter in a Fermionic Condensate

Abstract: We analyze the dynamics of a condensate of ultra-cold atomic fermions following an abrupt change of the pairing strength. At long times, the system goes to a non-stationary steady state, which we determine exactly. The superfluid order parameter asymptotes to a constant value. We show that the order parameter vanishes when the pairing strength is decreased below a certain critical value. In this case, the steady state of the system combines properties of normal and superfluid statesthe gap and the condensate f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
247
3
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(274 citation statements)
references
References 20 publications
19
247
3
2
Order By: Relevance
“…Previous studies of the BCS dynamics [3,7,[16][17][18][19] were performed in the weak-coupling regime when both 0i and …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of the BCS dynamics [3,7,[16][17][18][19] were performed in the weak-coupling regime when both 0i and …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies, motivated by experiments in cold atomic fermions, focused on quantum quenches, nonequilibrium conditions created by a sudden change in the superconducting coupling strength. Barankov et al [7], in a paper that set off a surge of modern research in this long-standing problem [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] in the context of quantum gases, found that for initial conditions close to the unstable normal state, the order parameter exhibits large anharmonic periodic oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Pairing correlations initially build up exponentially in time and then oscillate taking the form of soliton trains. If the system before the quench is in an equilibrium BCS state, and the quench is performed by changing abruptly the pairing coupling, then the stationary state can show a constant (but reduced) gap or can be gapless [11,19]. A classification of the allowed nonequilibrium behaviors arising from different initial conditions has been presented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In microcavities one has access to a range of non-equilibrium states, created for example by coherent pumping [23], and hence a laboratory for widely exploring mechanisms which create and preserve coherence. In atomic Bose gases the development of condensates has been studied both theoretically and experimentally [24,25,26], and there has been much recent interest in non-adiabatic phenomena involving coherent states of atomic Fermi gases [27,28,29].…”
Section: Introductionmentioning
confidence: 99%